Quantitative evaluation of silicon applications on wheat response to salinity: changes in photosynthetic pigments, chlorophyll fluorescence parameters, yield and yield components - Feghhenabi, Faride; Hadi, Hashem; Khodaverdiloo, Habib; van Genuchten, Martinus Th [UNESP]; Lake, Lachlan (Csiro Publishing, 2022)
Context. Salinity is a major cause of yield loss in wheat globally. Aims and Methods. To investigate the potential of silicon to minimise the effect of salinity in wheat, experiments were conducted using outdoor pots subjected to seven salinity treatments. Silicon (as potassium silicate K2SiO3) was applied as both a priming agent and foliar spray. Selected response functions were used to quantify wheat response to salinity as affected by silicon application. Key results. Concentration of chlorophyll a, chlorophyll b and carotenoid decreased by 4.2, 3.6 and 1.4 mg/g FW respectively with increasing salinity up to an electrical conductivity of 14 dS/m. Increasing salinity levels increased maximum variable chlorophyll fluorescence yield in a dark-adapted state and decreased the photochemical quenching coefficient, the non-photochemical quenching coefficient, nonphotochemical quenching, actual quantum yield of PSII electron transport in the light-adapted state, and the apparent photosynthetic electron transport rate. The maximal efficiency of PSII photochemistry in the dark-adapted state was not significantly influenced by salinity. The response functions showed that the salinity threshold value and the salinity at which a given trait was reduced by 50% (EC50) were 5.7 and 12.1 dS/m, respectively. Conclusions, The combined treatment of silicon (priming x foliar spray) was found to be the most effective, increasing salinity threshold value and EC50 by 32 and 2% respectively. implications. These findings give insight into the effects of salinity on wheat and demonstrate the potential of silicon applications to promote crop health in saline environments.
Keywords: abiotic stresses; chlorophyll fluorescence; foliar spray; plant production; priming; reduction function; soil salinity; yield